STRUKTUR VERBA DAN TIPE MEDIAL TINDAKAN BAHASA BALI. - I Nyoman Kardana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract This study deals with the types of action middle found in Balinese. Data was gained through observation and interview method to some Balinese speakers. The data obtained from the speakers was completed by data produced by the writer as the native speaker of Balinese. Based on the analysis it was found that the action middles in Balinese can be classified into ten types, they are middle of grooming, middle of body change, non-translational middle, translational middle, indirect middle, middle of emotion, middle of cognition, spontaneous middle, middle of natural reciprocal, and middle of emotive utterance. Seen from their verb structures, verbs used in the action middles in Balinese can be classified into (1) intransitive verbs and transitive verbs. The intransitive verbs are classified into zero intransitive (ZO), intransitive {ma-} (IMA), intransitive {ma-/-an}, and nasal intransitive (NI). The intransitive {ma-} is divided into intransitive {ma-} with noun as its base, intransitive {ma-} with zero transitive verb as its base, and intransitive {ma-} with pre-category as its base. Furthermore, the transitive verb is divided into zero transitive (ZT) and nasal transitive marked by N-, {N-/-ang}, and {N-/-in}. The base of the transitive verbs are verb, noun, adjective, and pre-category.